2019
DOI: 10.1155/2019/4892183
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Atypical Depression as an Early Feature of Pituitary Adenoma: A Case Report and Literature Review

Abstract: Pituitary adenomas are often diagnosed as incidental findings on brain imaging. We present the case of a 52-year-old African American female patient with long standing depressed mood prior to the incidental finding of a pituitary adenoma. We explore the possibility of certain mood symptoms prompting an early diagnosis of pituitary adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Contrary to the common belief that ESS is usually asymptomatic, two early studies of 43 [ 11 ] and 71 [ 12 ] cases reported a high frequency of psychological disorders [ 11 ] and 80.2% [ 12 ] of mental disorders, respectively. A literature search exploring the occurrence of psychiatric symptoms that may predate the objective pituitary findings, depression was reported in 71% of relevant papers [ 13 ]. On average, it took 11 years from initially documented clinical depression to an objective pituitary abnormality among 51% of cases with pituitary findings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the common belief that ESS is usually asymptomatic, two early studies of 43 [ 11 ] and 71 [ 12 ] cases reported a high frequency of psychological disorders [ 11 ] and 80.2% [ 12 ] of mental disorders, respectively. A literature search exploring the occurrence of psychiatric symptoms that may predate the objective pituitary findings, depression was reported in 71% of relevant papers [ 13 ]. On average, it took 11 years from initially documented clinical depression to an objective pituitary abnormality among 51% of cases with pituitary findings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature search exploring the occurrence of psychiatric symptoms that may predate the objective pituitary findings, depression was reported in 71% of relevant papers [ 13 ]. On average, it took 11 years from initially documented clinical depression to an objective pituitary abnormality among 51% of cases with pituitary findings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression in pituitary disorders such as PA and CP can be due to the presence of the CNS tumour itself as well as the impact of this on the individual. Additionally, excessive GH production, causing obesity, disruption of the HPA-axis and hypersecretion of ACTH, or deficiency in TSH and central hypothyroidism can lead to depressed mood (1182)(1183)(1184).…”
Section: 34(d) Isolated Optic Neuritismentioning
confidence: 99%